Pancreatoduodenectomy versus total pancreatectomy and simultaneous intraportal islet autotransplantation for periampullary cancer at high-risk of postoperative pancreatic fistula (XANDTX-trial): Protocol of a randomized controlled pilot trial - Sebastian Hempel; Fiona R. Kolbinger; Florian Oehme; Olga Radulova-Mauersberger; Janine Schmid; Undine Schubert; Florian Schepp; Stefan Bornstein; Sandra Korn; Evelyn Trips; Jürgen Weitz; Marius Distler; et al. (PLoS ONE, 2025)
Introduction Pancreatic surgery remains associated with significant morbidity. Pancreatoduodenectomy (PD) with high-risk stigmata for postoperative pancreatic fistula (POPF) may delay or hinder administration of adjuvant therapy. Total pancreatectomy (TP) prevents POPF-associated complications but implies permanent exocrine and endocrine insufficiency. Islet autotransplantation (IAT) has the potential to compensate endocrine function. Methods and analysis XANDTX is a single-centre randomized controlled pilot trial comparing high-risk PD with TP and simultaneous IAT in patients with periampullary cancer. After screening for eligibility and obtaining informed consent, a total of 32 adult patients will be intraoperatively randomized in a 1:1 ratio. The primary hypothesis is that TP with IAT prevents POPF-associated complications and leads to a shorter period to initiation of adjuvant therapy and a higher overall rate of adjuvant therapy administration. Secondary endpoints include perioperative morbidity and mortality, metabolic outcome, quality of life (QoL) and oncological long-term outcome. Each patient will be followed up for 5 years. Discussion The XANDTX pilot trial will aim to provide surgical and oncological feasibility and safety data of total pancreatectomy with simultaneous islet autotransplantation in management of resectable periampullary cancer. The results will form the basis for a further confirmatory controlled study. Trial registration This study was registered on ClinicalTrials.gov (NCT05843877) on February 27, 2023 and EudraCT (2023-507773-17-00) on April 18, 2024.